Persistent vascular dysfunction following an acute nonpharmacological reduction in blood pressure in hypertensive patients. Issue 6 (June 2022) - Fermoyle, Caitlin C.; Broxterman, Ryan M.; La Salle, D. Taylor; Ratchford, Stephen M.; Hopkins, Paul N.; Richardson, Russell S.; Trinity, Joel D.
Abstract : Background: Vascular dysfunction, an independent risk factor for cardiovascular disease, often persists in patients with hypertension, despite improvements in blood pressure control induced by antihypertensive medications. Methods: As some of these medications may directly affect vascular function, this study sought to comprehensively examine the impact of reducing blood pressure, by a nonpharmacological approach (5 days of sodium restriction), on vascular function in 22 hypertensive individuals (14 men/8 women, 50 ± 10 years). Following a 2-week withdrawal of antihypertensive medications, two 5-day dietary phases, liberal sodium (liberal sodium, 200 mmol/day) followed by restricted sodium (restricted sodium, 10 mmol/day), were completed. Resting blood pressure was assessed and vascular function, at both the conduit and microvascular levels, was evaluated by brachial artery flow-mediated dilation (FMD), reactive hyperemia, progressive handgrip exercise, and passive leg movement (PLM). Results: Despite a sodium restriction-induced fall in blood pressure (liberal sodium: 141 ± 14/85 ± 9; restricted sodium 124 ± 12/79 ± 9 mmHg, P  < 0.01 for both SBP and DBP), FMD (liberal sodium: 4.6 ± 1.8%; restricted sodium: 5.1 ± 2.1%, P  = 0.27), and reactive hyperemia (liberal sodium: 548 ± 201; restricted sodium: 615 ± 206 ml, P  = 0.08) were not altered. Similarly, brachial artery vasodilation during handgrip exercise was not different between conditions (liberal sodium: Δ0.36 ± 0.19 mm; restricted sodium: Δ0.42 ± 0.18 mm, P  = 0.16). Lastly, PLM-induced changes in peak blood flow (liberal sodium: 5.3 ± 2.5; restricted sodium: 5.8 ± 3.6 ml/min per mmHg, P  = 0.30) and the total vasodilatory response [liberal sodium: 2 (0.9–2.5) vs. restricted sodium: 1.7 (1.1–2.6) ml/min per mmHg; P  = 0.5] were also not different between conditions. Conclusion: Thus vascular dysfunction, at both the conduit and microvascular levels, persists in patients with hypertension even when blood pressure is acutely reduced by a nonpharmacological approach.